2016
DOI: 10.1007/s10346-016-0783-6
|View full text |Cite
|
Sign up to set email alerts
|

Does parameterization influence the performance of slope stability model results? A case study in Rio de Janeiro, Brazil

Abstract: We produce factor of safety (FOS) and slope failure susceptibility index (SFSI) maps for a 4.4-km 2 study area in Rio de Janeiro, Brazil, in order to explore the sensitivity of the geotechnical and geohydraulic parameterization on the model outcomes. Thereby, we consider parameter spaces instead of combinations of discrete values. SFSI is defined as the fraction of tested parameter combinations within a given space yielding FOS <1. We repeat our physically based calculations for various parameter spaces, emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…3 and 5) underlines the important impact of slope angle, and thus DTM quality, on model outputs. Neves Seefelder et al (2016) and Zieher et al (2017) identified slope angle as one of the most sensitive modeling parameters in TRIGRS, which is not surprising since slope failures are in general associated with higher slope angles (Liao et al, 2011). Even under greatly varying geotechnical or hydraulic input parameter settings, the same slope segments experience the highest likelihood of slope failure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…3 and 5) underlines the important impact of slope angle, and thus DTM quality, on model outputs. Neves Seefelder et al (2016) and Zieher et al (2017) identified slope angle as one of the most sensitive modeling parameters in TRIGRS, which is not surprising since slope failures are in general associated with higher slope angles (Liao et al, 2011). Even under greatly varying geotechnical or hydraulic input parameter settings, the same slope segments experience the highest likelihood of slope failure.…”
Section: Discussionmentioning
confidence: 91%
“…(Seyfried and Wilcox, 1995;Fan et al, 2016). Neves Seefelder et al (2016) suggest applying rather broad ranges of parameters for physically based approaches to be on the "safe side" as they yield results comparable in quality to those derived with best-fit narrow ranges. By acknowledging the fact that geotechnical and hydrological parameterswhen working on larger areas -are highly variable, uncertain, and often poorly known, narrow parameter ranges or even singular combinations of parameters come with the risk of being off target (Neves Seefelder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sliding surfaces most likely coincide spatially with geotechnically susceptible areas, layers or interfaces, spaced in a more or less irregular way. Even though much effort was put in sampling and testing, it appears hardly feasible to parameterize such patterns of localized patches of low soil strength, increased water input or increased hydraulic conductivity, or the effects of the vegetation (de Lima Neves Seefelder et al 2016). This means that either even more detailed studies including comprehensive material sampling and testing as well as regolith depth measurements, or appropriate techniques for a stochastic representation of the variability of the key parameters, are necessary for studies of single landslides or slopes.…”
Section: Discussionmentioning
confidence: 99%
“…Many deterministic approaches use the FoS to state whether a hillslope becomes unstable according to distinct physical parameters. Mergili et al (2014a) and De Lima Neves Seefelder et al (2016) emphasised that FoS-derived with a fixed set of geotechnical parameters-might fail to capture the details of a landscape. The wide range of root cohesion forces associated to different root systems would rather promote misinterpretations of the FoS due to the uncertainties associated with the dissimilarities of root distribution.…”
Section: Separated Vs Mixed Standsmentioning
confidence: 99%